Optimizing Digital Library Services to Support Teaching and Learning in Higher Education: A Strategic Governance Approach - saharudin saharudin; Regita Riani Putri (International Journal of Education and Teaching Zone, 2026)
Digital transformation has redefined university libraries as strategic digital service ecosystems that support teaching, learning, and institutional governance. Despite substantial investments in digital library infrastructure, empirical evidence on users’ perceptions of service quality within institutional governance frameworks remains limited, particularly in Indonesian higher education. This study evaluated students’ perceptions of digital library service quality within the SMART UNJA institutional governance framework and examined whether these perceptions differed across gender and faculty groups. A quantitative cross-sectional survey was conducted with 303 students selected through stratified random sampling. Data were collected using a validated questionnaire measuring six dimensions of digital library service quality: reliability, responsiveness, assurance, empathy, tangibility, and digital infrastructure. Descriptive statistics, independent-samples t-tests, and MANOVA were employed for data analysis. The findings indicate that students generally perceived digital library services positively across all dimensions, with tangibility receiving the highest ratings and empathy the lowest. No statistically significant differences were found across gender or faculty groups, suggesting a consistent service experience among users. These findings provide empirical evidence that the SMART UNJA governance framework supports equitable and user-centered digital library services while highlighting the importance of strengthening personalized service interactions. The study contributes to the growing literature on digital library service quality by offering evidence from an institutional digital governance perspective in higher education.